Emamectin Benzoate-Induced Hepatotoxicity in Rats with Special Reference to Protective Potential of Nigella sativa Oil - Madkour, DA; Ahmed, MM; Orabi, SH; Alkafafy, M; Korany, R; Khalifa, HK (Journal of the Hellenic Veterinary Medical Society, 2022)
This study was designed to explore the hepatotoxicity of emamectin in male rats and the possible effect of Nigella sativa oil (NSO) in ameliorating this. Twenty-eight male rats were used in this study. They were divided into four groups, Control group: rats orally administered distilled water; NSO group: rats administered NSO orally; EMB group: rats administered emamectin benzoate orally; and EMB+NSO group: rats orally co-administered NSO with EMB, with the administrations being performed every other day for 6 weeks. Body weight was measured, liver alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) activities were determined, and total protein and albumin levels were recorded. Histopathological examination of the liver was also performed, along with caspase-3 and TNF-α immunostaining of liver tissue. EMB treatment resulted in decreased body weight, while the co-administration of NSO modulated the EMB-induced alterations in body weight. There were also increases in the activities of serum ALT, AST, and ALP and decreases in total protein and albumin levels in the EMB group. Co-treatment with NSO significantly reduced serum ALT, AST, and ALP and improved total protein and albumin levels. Histopathological examination of the liver in the EMB group revealed the presence of different histopathological alterations that were improved by the co-administration of NSO. Immunostaining of caspase-3 and TNF-α in the liver revealed strong expression in the EMB-treated group. Meanwhile, the EMB+NSO group showed weak positivity for immunoreactive cells.